2021
DOI: 10.3390/ijerph18105364
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Balance Training with Stroboscopic Vision for Patients with Chronic Ankle Instability: A Single-Blinded Randomized Controlled Trial

Abstract: Chronic Ankle Instability (CAI) is one of the most common musculoskeletal dysfunctions. Stroboscopic vision (SV) training has been deemed to enhance somatosensorial pathways in this population group; nevertheless, until recently no studies have addressed the additional effects of this treatment option to the traditional therapeutic approach. Methods: To evaluate the effectiveness of a partial visual deprivation training protocol in patients with CAI, a randomized controlled trial was carried out. Patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 54 publications
0
18
1
Order By: Relevance
“…Both neuromuscular training and strength training groups improved all variables, with no differences between groups on dynamic balance, functional status, subjective feeling of instability, and ankle DFROM. In contrast with previous research [ 25 , 26 , 27 , 28 , 29 ], the control group improved dynamic balance and CAIT despite not receiving treatment.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Both neuromuscular training and strength training groups improved all variables, with no differences between groups on dynamic balance, functional status, subjective feeling of instability, and ankle DFROM. In contrast with previous research [ 25 , 26 , 27 , 28 , 29 ], the control group improved dynamic balance and CAIT despite not receiving treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…Self-reported physical function is reduced in subjects with CAI and could be measured with FAAM-ADL and FAAM-SPORT to determine the influence of CAI in daily living activities as well as sport-related activities [ 20 ]. Kim et al [ 28 ] found improvements in self-reported function in balance training and hop-stabilization tasks, and Ardakani et al [ 29 ] obtained similar results in an intervention consisting of hop-stabilization training in both FAAM-ADL and FAAM-SPORT subscales. These improvements agree with the obtained results where the NG group showed greater within-group change scores than SG and CG.…”
Section: Discussionmentioning
confidence: 94%
“…Against this background, optic flow perturbations might be a helpful tool that should be considered when developing rehabilitation programs, as they could help patients to decrease reliance on visual information during balance control and upregulate reliance on somatosensory information for motor programming ( Lee et al, 2021 ; Han et al, 2022 ). The implementation of this novel approach may enhance the activity of the somatosensory pathways to the postural system due to limited visual information input ( Kim et al, 2021 ). Future research is needed to investigate the effects of training programs that include optic flow perturbations on postural control in individuals with altered somatosensory input due to musculoskeletal injury or aging.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a systematic review published in 2021 27 only scanned three databases and analysed the shortterm effects of balance training. However, several relative randomised controlled trials (RCTs) published after the final retrieval deadline of April 2021, [28][29][30][31] It is essential to investigate the duration of treatment effects of balance training in patients with CAI for clinicians in the decision-making process. 32 Studies have defined 6 months post-intervention as a long-term effect assessment point for CAI.…”
Section: Open Accessmentioning
confidence: 99%
“…In addition, a systematic review published in 202127 only scanned three databases and analysed the short-term effects of balance training. However, several relative randomised controlled trials (RCTs) published after the final retrieval deadline of April 2021,28–31 and control interventions, such as whole-body vibration training and ROM training, have not been compared with balance training.…”
Section: Introductionmentioning
confidence: 99%